# Solve: x2 + 5x – (a2 + a – 6) = 0

Using splitting middle term, the middle term of the general equation is divided in two such values that:

Product = a.c

For the given equation a = 1 b = 5 c =

=

And either of their sum or difference = b

=

Thus the two terms are

Difference =

=

Product =

=

x[x + (a + 3)] - (a - 2)[x + (a + 3)] = 0

[x - (a - 2)][x + (a + 3)] = 0

[x - (a - 2)] = 0 or [x + (a + 3)] = 0

x = (a - 2) or x = - (a + 3)

Hence roots of equation are x = (a - 2)or - (a + 3)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Quiz | Knowing the Nature of Roots44 mins
Take a Dip Into Quadratic graphs32 mins
Foundation | Practice Important Questions for Foundation54 mins
Nature of Roots of Quadratic Equations51 mins
Getting Familiar with Nature of Roots of Quadratic Equations51 mins
Quadratic Equation: Previous Year NTSE Questions32 mins
Champ Quiz | Quadratic Equation33 mins
Understand The Concept of Quadratic Equation45 mins
Quiz | Lets Solve Imp. Qs of Quadratic Equation43 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses